BLENDED LEARNING FOR VOCATIONAL HIGH SCHOOL STUDENTS - Oktovianus Nau Lalian; Eveline Siregar; Murni Winarsih (Kwangsan: Jurnal Teknologi Pendidikan, 2021)
The aimed of this study was to develop a blended learning for vocational students of light vehicle power expertise program in the learning process as a learning strategy to overcome the problem of lack of face-to-face time in class. The procedure for developing blended learning used was PEDATI model (learning, deepening, applying, measuring) as design instructional for blended learning. Data collection techniques used were observation, interview, and questionnaires. Data analysis techniques used was descriptive qualitative. The development of blended learning through the PEDATI model will be very effective for the achievement of learning objectives optimally and efficiency in learning time in class. AbstrakTujuan penelitian ini adalah mengembangkan blended learning bagi siswa SMK program keahlian tenaga kendaraan ringan dalam proses pembelajaran sebagai suatu strategi pembelajaran untuk mengatasi masalah kekurangan waktu tatap muka di kelas. Prosedur pengembangan blended learning dengan model PEDATI (Pelajari, Dalami, Terapkan, dan Evaluasi) sebagai model desain pembelajaran blended learning. Teknik pengumpulan data melalui observasi, wawancara, dan kuesioner. Teknik analisis data yang digunakan adalah deskriptif kualitatif. Pengembangan blended learning dengan prosedur PEDATI  akan sangat efektif untuk pencapaian tujuan pembelajaran secara optimal dan efisiensi waktu pembelajaran di kelas.